2018
DOI: 10.3390/nu10070939
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Dietary Cholesterol on Chronic Metabolic Diseases through Studies in Rodent Models

Abstract: The development of certain chronic metabolic diseases has been attributed to elevated levels of dietary cholesterol. However, decades of research in animal models and humans have demonstrated a high complexity with respect to the impact of dietary cholesterol on the progression of these diseases. Thus, recent investigations in non-alcoholic fatty liver disease (NAFLD) point to dietary cholesterol as a key factor for the activation of inflammatory pathways underlying the transition from NAFLD to non-alcoholic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 90 publications
(115 reference statements)
1
21
0
2
Order By: Relevance
“…Recent studies in animal models indicate that the accumulation of fat and cholesterol in the hepatocyte are key factors for the activation of the inflammatory pathways involved in the transition from NAFLD to NASH and to hepatocellular carcinoma in animal models [ 52 ]. The intake of carotenoid-rich diets (groups LC12.75 and HC25.5) decreased the concentrations of total cholesterol and liver triglycerides, as has been found in other investigations with the supplementation of lutein, lycopene, astaxanthin and β-carotene [ 14 , 16 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in animal models indicate that the accumulation of fat and cholesterol in the hepatocyte are key factors for the activation of the inflammatory pathways involved in the transition from NAFLD to NASH and to hepatocellular carcinoma in animal models [ 52 ]. The intake of carotenoid-rich diets (groups LC12.75 and HC25.5) decreased the concentrations of total cholesterol and liver triglycerides, as has been found in other investigations with the supplementation of lutein, lycopene, astaxanthin and β-carotene [ 14 , 16 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intake of carotenoid-rich diets (groups LC12.75 and HC25.5) decreased the concentrations of total cholesterol and liver triglycerides, as has been found in other investigations with the supplementation of lutein, lycopene, astaxanthin and β-carotene [ 14 , 16 , 53 , 54 ]. The livers of the rats from the LC12.75 and HC25.5 groups, in addition to having a lower steatosis score than that of the CD group, showed less cholesterol accumulation, possibly due to its mobilization by plasma HDL [ 52 , 53 ]. This could explain the decrease in the concentration of cholesterol in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of dietary cholesterol on atherosclerosis has apparently been largely overestimated [ 2 , 3 ] and more recent recommendations for cardio-protective diets do not include the previously suggested radical reduction of cholesterol intake [ 4 ]. Although from the point of view of atherosclerosis, dietary cholesterol might be less relevant than previously assumed, it has reentered the focus of interest because of its potential role in the progression of non-alcoholic fatty liver disease (NAFLD) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that HFHC diet-induced histopathological changes in the livers of mice were accompanied by a significant accumulation of small cholesterol-containing droplets, which contained abundant cholesterol crystals [3] and free cholesterol [36]. The impact of dietary cholesterol was recently demonstrated to be a key factor in the transition from simple steatosis to NASH [37]. The accumulation of cholesterol crystals and free cholesterol in the liver may lead to a dysregulated cholesterol synthesis pathway and cause liver damage [3,38].…”
Section: Discussionmentioning
confidence: 99%